Epidemiology and tumor microenvironment of ocular surface and orbital tumors on growth and malignant transformation - Ou, Shangkun; Lin, Yuan; Zhang, Yujie; Shi, Ke; Wu, Huping (Frontiers in Oncology, 2024)
The ocular surface and orbit constitute unique microenvironments in the human body. Current advances in molecular research have deepened our understanding of tumor development in these regions. Tumors exhibit greater heterogeneity compared to normal tissues, as revealed by pathological and histological examinations. The tumor microenvironment (TME) plays a crucial role in the proliferation and progression of cancer cells. Factors from the external environment or the body’s own inflammation and microcirculation interact within the TME, maintaining a delicate balance. Disruption of this balance, through uncontrolled signal pathway activation, can transform normal or benign tissues into malignant ones. In recent years, various systemic immunotherapies have been developed for cancer treatment. This study reviews the epidemiology of ocular surface and orbital tumors include squamous cell carcinoma, basal cell carcinoma, sebaceous carcinoma and lymphoma in conjunction with their occurrence, growth, and underlying mechanisms. We propose that by examining clinical histopathological images, we can identify specific and shared microscopic features of tumors. By collecting, classifying, and analyzing data from these clinical histopathological images, we can pinpoint independent diagnostic factors characteristic of tumors. We hope this study provides a basis for future exploration of the mechanisms underlying different ocular diseases.